2020
DOI: 10.3390/polym12102354
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties of Polychloroprene Rubbers in Tension and Compression during Ageing

Abstract: Being able to predict the lifetime of elastomers is fundamental for many industrial applications. The evolution of both tensile and compression behavior of unfilled and filled neoprene rubbers was studied over time for different ageing conditions (70 °C, 80 °C and 90 °C). While Young’s modulus increased with ageing, the bulk modulus remained almost constant, leading to a slight decrease in the Poisson’s ratio with ageing, especially for the filled rubbers. This evolution of Poisson’s ratio with ageing is often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In another word it may be clarify aged samples relatively shows the lower elongation because of it recuperate the properties in coarse of ageing treatment. Similar natures of higher values of Poisson's ratios are observed for bearing pad rubber because of the higher elongation of bearing pad rubber [25,26].…”
Section: Poisson's Ratiosupporting
confidence: 66%
“…In another word it may be clarify aged samples relatively shows the lower elongation because of it recuperate the properties in coarse of ageing treatment. Similar natures of higher values of Poisson's ratios are observed for bearing pad rubber because of the higher elongation of bearing pad rubber [25,26].…”
Section: Poisson's Ratiosupporting
confidence: 66%
“…Thus, it can be concluded that the elastic strain resulting from the application of a given stress for Act8-containing vulcanizates was smaller than for elastomers without this accelerator [57]. The Young's modulus (E) presented in Table 4 is a measure of the stiffness of the material and depends on the crosslink density of elastomer [56]. As the stiffness of the tested vulcanizates increased with the crosslink density, their Young's modulus was also increased.…”
Section: Influence Of the Dibenzyldithiocarbamate Accelerator On The ...mentioning
confidence: 95%
“…The results are given in Table 4, whereas the stress-strain curves are shown in Figure 3. The Young's modulus (E) presented in Table 4 is a measure of the stiffness of the material and depends on the crosslink density of elastomer [56]. As the stiffness of the tested vulcanizates increased with the crosslink density, their Young's modulus was also increased.…”
Section: Influence Of the Dibenzyldithiocarbamate Accelerator On The ...mentioning
confidence: 99%
“…An accelerated aging test is conducted by intensifying the factors that accelerate aging by using laboratory equipment to create conditions that exceed the normal service range [ 3 , 4 , 5 , 10 ]. The service life is predicted by modeling the changes in important mechanical properties, including the shore hardness, tension, impact, modulus, thermal decomposition, compression set (CS), and fatigue, under accelerated aging and setting reliability criteria [ 3 , 4 , 5 , 6 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%